A stance-taking study of wkwk as laughter in WhatsApp-based Indonesian speaking youth conversation - Widyatmoko, Edelleit Rose; Kushartanti, Bernadette (Indonesian Journal of Applied Linguistics, 2024)
Laughter, often overlooked as a mere emotional outlet, is a complex phenomenon with its unique charm. Online laughter, in particular, seems to differ significantly in terms of its paralanguage features from face-to-face laughter. Building on our prior understanding of how laughter and youth language is used in face-to-face communication, studying online laughter in youth conversation can provide insights into the types of information that are typically conveyed nonverbally. This is important because laughter often conveys a wealth of essential information that is not explicitly stated in the words that are used. This study takes a close look at “wkwk”, one of the Indonesian expressions of laughter in social media. This study aims to examine how the use of "wkwk" reflects interlocutors' self-positioning across different social contexts in WhatsApp-based Indonesian youth conversation. Through conversation analysis (Schegloff, 2007) and stance-taking theory (DuBois, 2007), this study examines the utterances made by interlocutors in producing laughter in chats. The findings reveal a similarity between “wkwk” and other forms of laughter in previous studies, which are closely bound to the laughable context of the conversation that serves as a key to indicate Indonesian youth language. However, the use of “wkwk” is specifically shown to indicate closeness and bond reinforcement among interlocutors. In conclusion, within the Indonesian social context of laughter, “wkwk” as a linguistic tool can facilitate the interlocutors' expression of closeness and their positioning of self and others within the online conversation.